2015
DOI: 10.1080/02678292.2015.1044578
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous liquid crystal alignment on poly(vinylidene fluoride-trifluoroethylene) films subjected to ion-beam irradiation

Abstract: We demonstrate homogeneous and uniform liquid crystal (LC) alignment on poly(vinylidene fluoride-trifluoroethylene) [PVDF-TrFE] films using ion-beam (IB) irradiation and a performance improvement of twisted nematic (TN) cells using IB-irradiated PVDF-TrFE films. Spontaneous ferroelectricity of the PVDF-TrFE films was modified by IB irradiation, which affected the LC alignment properties. The variation in the pre-tilt angles of the LC molecules on the IB-irradiated PVDF films is attributed to surface reformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 27–29 Alignment and electro-optical properties of twisted nematics sandwiched between PVDF-based films are reported in recent papers. 30,31 An experimental evidence of the strong impact of the remnant polarization of PVDF-based polymer on the alignment of liquid crystals has been shown for polymer dispersed liquid crystals (PDLC). 32,33 Results presented in Holländer et al 33 were obtained using cyanobiphenyl-based liquid crystals characterized by a relatively high concentration of residual ions.…”
Section: Introductionmentioning
confidence: 99%
“… 27–29 Alignment and electro-optical properties of twisted nematics sandwiched between PVDF-based films are reported in recent papers. 30,31 An experimental evidence of the strong impact of the remnant polarization of PVDF-based polymer on the alignment of liquid crystals has been shown for polymer dispersed liquid crystals (PDLC). 32,33 Results presented in Holländer et al 33 were obtained using cyanobiphenyl-based liquid crystals characterized by a relatively high concentration of residual ions.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Shah et al demonstrated the capability of PVDF-TrFE copolymers to serve as LC alignment layers when treated with corona poling. 21 In addition, we demonstrated that uniform LC alignment can be achieved on the PVDF-TrFE films fabricated at a low temperature of 135 • C. 22 To align LC molecules on the LC alignment film surface during LCD fabrication, rubbing methods are conventionally used. However, there are some disadvantages arising from mechanical contact with the alignment layers, including the accumulation of electrostatic charge and the generation of fine dust, which degrade LCD quality.…”
mentioning
confidence: 99%